Genetic characterization of phenicol-resistant Escherichia coli and role of wild-type repressor/regulator gene (acrR) on phenicol resistance - Yaqoob, Muhammad; Wang, Li Ping; Kashif, Jam; Memon, Javed; Umar, Sajid; Iqbal, Muhammad Farooq; Fiaz, Muhammad; Lu, Cheng-Ping (Folia microbiologica, 2018)
The genetic basis for phenicol resistance was examined in 38 phenicol-resistant clinical Escherichia coli isolates from poultry. Out of 62 isolates, 38 showed resistance for chloramphenicol and nine for florfenicol, respectively. Each strain also demonstrated resistance to a variety of other antibiotics. Molecular detection revealed that the incidence rates of the cat1, cat2, flo, flo-R, cmlA, and cmlB were 32, 29, 18, 13, 0, and 0%, respectively. Nineteen strains were tolerant to organic solvents. PCR amplification of the complete acrR (regulator/repressor) gene of five isolates revealed the amino acid changes in four isolates. DNA sequencing showed the non-synonymous mutations which change the amino acid, silent mutation, and nucleotide deletion in four isolates. MY09C10 showed neither deletion nor mutation in nucleotide. The AcrA protein of the AcrAB multidrug efflux pump was overexpressed in these strains. Complementation with a plasmid-borne wild-type acrR gene reduced the expression level of AcrA protein in the mutants and partially restored antibiotic susceptibility one- to fourfold. This study shows that mutations in acrR are an additional genetic basis for phenicol resistance.
Keywords: nemoci drůbeže; Microbial Sensitivity Tests; membránové transportní proteiny; proteiny z Escherichia coli; DNA bakterií; Genetic Complementation Test; mnohočetná bakteriální léková rezistence; Chickens; Genes, Bacterial; Chloramphenicol Resistance; mutace; mikrobiální testy citlivosti; Escherichia coli; Genotype; antibakteriální látky; zvířata; Membrane Transport Proteins; represorové proteiny; Escherichia coli Proteins; Drug Resistance, Multiple, Bacterial; regulace genové exprese u bakterií; Poultry Diseases; DNA, Bacterial; kur domácí; Repressor Proteins; Anti-Bacterial Agents; bakteriální geny; rezistence na chloramfenikol; Gene Expression Regulation, Bacterial; genotyp; Animals; Mutation; testy genetické komplementace